Judging from experience : law, praxis, humanities - Gaakeer, A. M. P. (Edinburgh critical studies in law, literature and the humanities., 2019)
Combining her expertise in legal theory and judicial practice in a continental-European civil-law system, Jeanne Gaakeer explores the intertwinement of legal theory and practice to develop a humanities-inspired methodology for both the academic interdisciplinary study of law and literature and for legal practice.